A 10-month-old boy with phacomatosis cesioflammea. - Bukulmez, A.; Haktanir, N.T.; Koken, R.; Melek, H.; Yavas, G.; Dõlek, F.H. (European Journal of Pediatric Dermatology, 2007)
Phacomatosis pigmentovascularis is a rare skin disorder, described as a cutaneous malformation with vascular and melanocytic components. In a newer and simpler classification of Happle in 2005, there are only three distinct types of phacomatosis pigmentovascularis, apart from a group of unclassifiable forms. The three well-established forms are called phacomatosis cesioflammea, phacomatosis spilorosea and phacomatosis cesiomarmorata. We present a 10-month-old boy with phacomatosis cesioflammea.